Modular Organization of the ESX-5 Secretion System in Mycobacterium tuberculosis - Shah, Swati; Briken, Volker (Frontiers in Cellular and Infection Microbiology, 2016)
Mycobacteria utilize type VII secretion systems (T7SS) to export many of their important virulence proteins. The T7SS encompasses five homologous secretion systems (ESX-1 to ESX-5). Most pathogenic mycobacterial species, including the human pathogen Mycobacterium tuberculosis, possess all five ESX systems. The ESX-1, -3 and -5 systems are important for virulence of mycobacteria but the molecular mechanisms of their secretion apparatus and the identity and activity of secreted effector proteins are not well characterized. The different ESX systems show similarities in gene composition due to their common phylogenetic origin but recent studies demonstrate mechanistic as well as functional variations between the systems. For example, the ESX-1 system is involved in lysis of the phagosomal membrane and phagosomal escape of the bacteria while the ESX-5 system is required for mycobacterial cell wall stability and host cell lysis. Mechanistically, the ESX-1 substrates show interdependence during secretion while the ESX-5 system may use a duplicated four-gene region (ESX-5a) as an accessory system for transport of a subset of proteins of the ESX-5 secretome. In the present review we will provide an overview of the molecular components of the T7SS and their function with a particular focus on the ESX-5 system.